2011
DOI: 10.1002/aic.12538
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the liquid feed distribution in gas‐solid fluidized beds by nozzle pulsations (induced by solenoid valve)

Abstract: In this work, it was found that spray nozzles pulsations greatly improved the liquid feed spray distribution on fluidized bed particles. Pulsating a spray nozzle doubled its nozzle performance index at various operating conditions. The objective of this study was to impose fluctuations of well‐defined frequency and amplitude on the liquid spray to investigate potentially beneficial effects of fluctuations on the liquid feed distribution on the particles in the fluidized bed. Three sets of experiments were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The jet penetration is predominantly related to the liquid flow rate, as shown in Figure 14, and there is a weak relationship between gas flow rate and jet penetration (Figure 15). In addition, this finding can be confirmed by the results obtained previously using a solenoid valve to impose pulsations of well‐defined frequency and described in the authors' previous work 15. Figure 16 shows that, for these earlier experiments, there also was a relationship between instantaneous liquid flow rate and jet penetration.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The jet penetration is predominantly related to the liquid flow rate, as shown in Figure 14, and there is a weak relationship between gas flow rate and jet penetration (Figure 15). In addition, this finding can be confirmed by the results obtained previously using a solenoid valve to impose pulsations of well‐defined frequency and described in the authors' previous work 15. Figure 16 shows that, for these earlier experiments, there also was a relationship between instantaneous liquid flow rate and jet penetration.…”
Section: Resultssupporting
confidence: 84%
“…On the other hand, the authors' previous work15 showed that pulsations with the right characteristics can be very beneficial. For example, imposing liquid flow pulsations with a solenoid valve closing and opening with a frequency of 1–10 Hz nearly doubled the NPI.…”
Section: Introductionmentioning
confidence: 98%
“…This can easily lead to the destabilization of the bed, and plugging of the product disengagement lines. Unfortunately, the majority of the open scientific literature in this field appears to be dedicated to studying how best to wet particles in an FCC solid–gas bed, which is pretty much the opposite of what we want to do here. What is clear from the open patent literature is that the number and positioning of the nozzles in the bed, their depth of penetration and orientation, the velocity and direction of the liquid stream will all be very important parameters in obtaining optimal liquid injection conditions .…”
Section: Fundamentals Of Condensed Mode Cooling In Modern Pe Plantsmentioning
confidence: 97%
“…Sabouni et al used the active conductance technique from a previous study to study the effect of nozzle pulsations on the quality of liquid‐solid contact in a laboratory scale fluidized bed. The study focussed on gas‐line pulsations that were milder than those of previous studies and where the instantaneous gas‐to‐liquid (G/L) ratio in the nozzle was never reduced all the way to 0 wt %.…”
Section: Introductionmentioning
confidence: 99%